Sosialisasi Penerapan PSAK 115 pada Transaksi Penjualan di PT Alfa Scorpii Setia Budi (Yamaha Medan) - Mutia Riska Faridani; Rifdah Riyan Dara; Corinna Wongsosudono; Sovia Lolita Apriani Pardede; Ripka Seriidahnaita Ginting; Esty Pudyastuti (Lembaga Pengembangan Kinerja Dosen, 2025)
PSAK 115 is an Indonesian accounting standard that governs revenue recognition from contracts with customers. Previously known as PSAK 72, the standard adopts IFRS 15 and replaces PSAK 23 and PSAK 34. PSAK 115 requires that revenue be recognized when the entity has fulfilled its performance obligations to the customer, ensuring revenue is recognized at the right time, in the correct amount, and with proper disclosure. In practice, however, implementing PSAK 115 poses challenges. Common issues include difficulties in determining the timing of revenue recognition, identifying performance obligations, transferring control, and allocating the transaction price to multiple obligations within a single contract. This community service was conducted at PT Alfa Scorpii Medan with the aim of enhancing the understanding of financial and administrative staff regarding PSAK 115. The method used involved presentations and interactive discussions. The results showed that participants understood the five-step revenue recognition model and the importance of contract-based reporting. It is expected that this activity will encourage the company to apply PSAK 115 more accurately, leading to financial reports that are more reliable, relevant, and useful for users’ decision-making processes.